Role of Swallowing Therapy in Preventing Aspiration Pneumonia in Patients with Stroke having Dysphagia - Nauman, Bisma; Tassadaq, Naureen (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the effectivity of swallowing therapy in prevention of aspiration pneumonia in patients with acute stroke with dysphagia admitted to the Intensive Care Unit.Study Design: Prospective comparative study.Place and Duration of Study: Department of Rehabilitation Medicine, Fauji Foundation Hospital, Rawalpindi Pakistan, from Jun-Dec 2023Methodology: A total of 120 patients were recruited, patients were randomly divided into two groups. Group-S (n=60) receivied swallowing therapy and Group-N (n=60) received standard nursing care for oral feed according to institutional protocol. Primary variables studied were median scores of the Functional Oral Intake Scale (FOIS) (Scored 1-7) and Swallow Function Score System (SFSS) (Scored 0-6) evaluated every day and complied after 10 days along with incidence of aspiration pneumonia and necessity to shift to NG feed in case of complete oral feed failure.Results: Median functional oral intake scale was 4.00 (0.00) in Group-N versus 6.00 (0.00) in Group-S (p